Changes in cross sectional area of inferior vena cava during exercise in water - Sho, O.; Kazuki, N.; Kumiko, O.; Kazutoshi, S.; Daisuke, N.; Takeshi, O.; Eri, O.; Natuki, S.; Hirosi, K.; Futoshi, O.; Toussaints, H. M. (Biomechanics and Medicine in Swimming X, 2006)
The purpose of the present study was to investigate the cross sectional area of inferior vena cava changes during exercises in water. Six subjects voluntarily participated in this study and performed an arm cranking exercise program under the four experimental conditions (20% V02max, 40% V02max, 60% V02max and control). Water temperature was 30 degrees C. Water depth was axilla. Heart rate and cross sectional area of inferior vena cava were measured by radiotelemetric electrocardiography and B-mode echocardiography, respectively. The cross sectional area of inferior vena cava decreased during the exercise program, and there was a significant relationship between the cross sectional area and intensity of the exercise program (p< 0.05). The findings of the study indicated that venous return had been keeping the volume during the low intensity exercise program and that had been changing the treatment from volume to velocity during the high intensity exercise program.